EFFECTS OF BANANA PSEUDOSTEM COMPOST RATES IN GROWING MEDIA ON GROWTH OF BLACK PEPPER (Piper nigrum L.) SEEDLINGS - Ansyori (RADJA PUBLIKA, 2026)
This study aimed to identify the most effective dosage of banana stem compost as a growing medium for black pepper seedlings (Piper nigrum L.). The experiment was arranged using a single-factor Randomized Block Design (RBD) consisting of five compost dosages: R0 (soil without compost), R1 (100 g compost/kg soil), R2 (200 g compost/kg soil), R3 (300 g compost/kg soil), and R4 (400 g compost/kg soil). Each treatment was replicated five times, resulting in 25 experimental units, with each unit consisting of five pepper seedlings. The observed variables included shoot length, number of leaves, root length, fresh weight, and dry weight of seedlings at 12 weeks after transplanting. Data were analyzed using analysis of variance (ANOVA), followed by Bartlett’s test for homogeneity and Tukey’s test to examine data additivity. When the F-test indicated significant effects, orthogonal polynomial analysis at the 5% and 1% significance levels was conducted.The results showed that banana stem compost significantly influenced shoot length, number of leaves, and root length, but did not significantly affect fresh and dry biomass. The optimal dosage was 300 g compost/kg soil, which supported balanced growth above and below the ground. Overall, banana stem compost demonstrated strong potential as a locally available organic material for pepper seedling production.